Instrumental, Vocal and Choir Theatre of Juris Karlsons - Vecumnieks, Andris (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of this article is to introduce the instrumental, vocal and choir music of the Latvian composer Juris Karlsons (*1948) in the context of music theatricality research. The article is based on discoveries and conclusions outlined in the doctoral thesis “The Theatricality Phenomenon in Music. Theatrical Space of Juris Karlsons”. The author introduces the current issues of theory and artistry in the instrumental theatre genre, as well as the contribution of Juris Karlsons to this genre and composition technique of the late 20th century. The thesis employs the following research methods: - theoretical methods (research studies): method of abstract analysis (gathering and evaluation with the purpose to create a general background) – studies of theatricality theory, studies of musical theatricality theory, analysis of Karlsons’ oeuvre; - methods of musicological analysis: approach to Karlsons’ works based on the genre analysis and classification method, defining and describing of the immanent characteristics, as well as musical style analysis method; - empirical and deductive methods (contributed from personal experience) – research, comparison and evaluation (determination of tendencies and guidelines), personal perception experience, observations and discoveries, writing and publishing articles for scientific conferences, music history lectures at JVLMA, secondary music schools and other institutions, own conductor’s experience; - semiotic method (significance of a system of symbols in Karlsons’ oeuvre); - data processing methods – evaluation, comparative analysis and systematization, including hypothetical modelling; - comparative research methods, providing parallel view comparison of musical practices, Karlsons’ oeuvre, as well as other means of expression in music and other arts – music and theatre, music and literature, music and visual arts; - methods of selection – evaluation of scientific research works and selection of analytical works; - field research methods – interviews with Karlsons and his contemporaries.